IMPLEMENTASI NILAI 3K (KERJA SAMA, KETULUSAN, KEPEDULIAN) DALAM PEMBENTUKAN KARAKTER SISWA DI SEKOLAH SANT’EGIDIO - Sisca Aulia; Chellsy Christine Afandi; Selina Kurnia; Stenly Bambang Yeremia Wantah; Nathaniel Christianto Kariodimedjo (Jurnal Serina Abdimas, 2026)
The 3K values learning program, Cooperation, Sincerity, and Caring—is designed to shape the character of Sant'Egidio School students who are socially minded, empathetic, and oriented towards togetherness. This community service activity aims to instill and strengthen the 3K character values, namely Caring, Cooperation, and Sincerity, in elementary school-aged children through an interactive communication approach. This school is held every Sunday using the pendopo or front hallway facilities at Santo Lukas School, Sunter. This learning activity is attended by approximately 50 children, most of whom come from families with economic limitations. This community service activity in the field of communication aimed to instill and strengthen the 3K character values Care, Cooperation, and Sincerity among elementary school children through an interactive communication approach. The program was implemented using an experiential learning method that included interactive material delivery, educational quizzes, and a creative workshop where participants made bracelets symbolizing each 3K value. This approach was designed to help children internalize moral values through enjoyable, collaborative, and practical activities. The results showed increased enthusiasm, active participation, and improved understanding of the meaning and application of the 3K values in daily life. Positive behavioral changes were also observed, including greater empathy toward peers, stronger teamwork, and sincere attitudes in social interactions. These findings demonstrate that communicative and participatory approaches are effective in shaping character development among elementary school children, particularly in non-formal educational contexts. This activity is expected to serve as a model for similar programs aimed at strengthening character education through communication-based learning in educational institutions.   ABSTRAK Program pembelajaran nilai 3K, yaitu Kerja Sama, Ketulusan, dan Kepedulian, dirancang untuk membentuk karakter siswa Sekolah Sant’Egidio yang berjiwa sosial, empatik, dan berorientasi pada kebersamaan. Kegiatan pengabdian masyarakat ini bertujuan untuk menanamkan dan memperkuat nilai-nilai karakter 3K, yaitu Kepedulian, Kerja Sama, dan Ketulusan, pada anak-anak usia sekolah dasar melalui pendekatan komunikasi interaktif. Sekolah ini diselenggarakan setiap hari Minggu dengan memanfaatkan fasilitas pendopo atau selasar depan kelas di Sekolah Santo Lukas, Sunter. Kegiatan belajar ini diikuti oleh sekitar 50 anak yang sebagian besar berasal dari keluarga yang memiliki keterbatasan ekonomi. Kegiatan ini dilaksanakan dengan metode pembelajaran berbasis pengalaman yang mencakup penyampaian materi interaktif, kuis edukatif, serta workshop pembuatan gelang yang merepresentasikan makna simbolik dari setiap nilai 3K. Pendekatan ini dirancang untuk memudahkan anak-anak memahami nilai-nilai karakter melalui kegiatan yang menyenangkan, kolaboratif, dan aplikatif. Hasil pelaksanaan menunjukkan bahwa peserta menunjukkan peningkatan antusiasme, partisipasi aktif, serta pemahaman yang lebih baik terhadap makna dan penerapan nilai 3K dalam kehidupan sehari-hari. Selain itu, perubahan perilaku positif tampak melalui meningkatnya rasa kepedulian terhadap teman sebaya, kemampuan bekerja sama dalam kelompok, serta ketulusan dalam membantu orang lain. Temuan ini menegaskan bahwa pendekatan komunikatif dan partisipatif efektif diterapkan dalam pembentukan karakter anak usia sekolah dasar, khususnya di lingkungan pendidikan nonformal. Kegiatan ini diharapkan menjadi model pengabdian yang dapat direplikasi untuk memperkuat pendidikan karakter berbasis komunikasi di berbagai institusi pendidikan.